OXYGEN ISOTOPE CONSTRAINTS ON THE ORIGIN AND DIFFERENTIATION OF THE MOON - Spicuzza M.J.; Valley J.W.; Day J.M.D.; Taylor L.A. (My University, 2007)
We report new high-precision laser fluorination three-isotope oxygen data for lunar materials. Terrestrial silicates with a range of δ18O values (- 0.5 to 22.9‰) were analyzed to independently determine the slope of the terrestrial fractionation line (TFL; λ = 0.5259 ± 0.0008; 95% confidence level). This new TFL determination allows direct comparison of lunar oxygen isotope systematics with those of Earth. Values of Δ17O for Apollo 12, 15, and 17 basalts and Luna 24 soil samples average 0.01‰ and are indistinguishable from the TFL. The δ18O values of high- and low-Ti lunar basalts are distinct. Average whole-rock δ18O values for low-Ti lunar basalts from the Apollo 12 (5.72 ± 0.06‰) and Apollo 15 landing sites (5.65 ± 0.12‰) are identical within error and are markedly higher than Apollo 17 high-Ti basalts (5.46 ± 0.11‰). Evolved low-Ti LaPaz mare-basalt meteorite δ18O values (5.67 ± 0.05‰) are in close agreement with more primitive low-Ti Apollo 12 and 15 mare basalts. Modeling of lunar mare-basalt source composition indicates that the high- and low-Ti mare-basalt mantle reservoirs were in oxygen isotope equilibrium and that variations in δ18O do not result from fractional crystallization. Instead, these differences are consistent with mineralogically heterogeneous mantle sources for mare basalts, and with lunar magma ocean differentiation models that result in a thick feldspathic crust, an olivine-pyroxene-rich mantle, and late-stage ilmenite-rich zones that were convectively mixed into deeper portions of the lunar mantle. Higher average δ18O (WR) values of low-Ti basalts compared to terrestrial mid ocean ridge basalts (Δ=0.18‰) suggest a possible oxygen isotopic difference between the terrestrial and lunar mantles. However, calculations of the δ18O of lunar mantle olivine in this study are only 0.05‰ higher than terrestrial mantle olivine. These observations may have important implications for understanding the formation of the Earth-Moon system. © 2006 Elsevier B.V. All rights reserved.
Keywords: LAPAZ; LASER FLUORINATION; LUNAR MAGMA OCEAN; MARE BASALTS; MOON; OXYGEN ISOTOPES; TFL